2020
DOI: 10.1017/s0030605319000176
|View full text |Cite
|
Sign up to set email alerts
|

Unsustainable harvest of water frogs in southern Turkey for the European market

Abstract: Frogs have been harvested from the wild for the last 40 years in Turkey. We analysed the population dynamics of Anatolian water frogs (Pelophylax spp.) in the Seyhan and Ceyhan Deltas during 2013–2015. We marked a total of 13,811 individuals during 3 years, estimated population sizes, simulated the dynamics of a harvested population over 50 years, and collated frog harvest and export statistics from the region and for Turkey as a whole. Our capture estimates indicated a population reduction of c. 20% per year,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…bedriagae , P. kurtmuelleri , P. ridibundus , and P. shqipericus ), have been introduced outward their natural ranges (e.g., to Belgium, France, Italy, and Switzerland), where they became invasive (Domeneghetti et al, 2013; Dubey et al, 2014; Dufresnes et al, 2017; Holsbeek et al, 2008, 2010). Recently, Çiçek et al (2021) have indicated that Turkey is an important country for the water frog trade. For more than 40 years, live animals have been exported from Turkey to European countries, mainly to France, Italy, Switzerland, and Albania, less to Greece, Spain, and Lebanon (Çiçek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bedriagae , P. kurtmuelleri , P. ridibundus , and P. shqipericus ), have been introduced outward their natural ranges (e.g., to Belgium, France, Italy, and Switzerland), where they became invasive (Domeneghetti et al, 2013; Dubey et al, 2014; Dufresnes et al, 2017; Holsbeek et al, 2008, 2010). Recently, Çiçek et al (2021) have indicated that Turkey is an important country for the water frog trade. For more than 40 years, live animals have been exported from Turkey to European countries, mainly to France, Italy, Switzerland, and Albania, less to Greece, Spain, and Lebanon (Çiçek et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Çiçek et al (2021) have indicated that Turkey is an important country for the water frog trade. For more than 40 years, live animals have been exported from Turkey to European countries, mainly to France, Italy, Switzerland, and Albania, less to Greece, Spain, and Lebanon (Çiçek et al, 2021). During the export, the live animals can carry their parasites and, after successful introduction, can spread them to non‐native areas.…”
Section: Discussionmentioning
confidence: 99%
“…2,3). In recent decades there have been four major source regions exporting edible frogs or body parts (wild and/or farmed) into the EU: (1) East Asia, i.e., China and Taiwan (Warkentin et al 2009;Altherr et al 2011;Shreshta 2019) (Niekisch 1986;le Serrec 1988;Warkentin et al 2009), and (4) eastern Europe i.e., Turkey and Albania (Warkentin et al 2009;Şereflişan and Alkaya 2016;Çiçek et al 2021).…”
Section: Major Suppliers Of Species For the Frogs' Legs Industry In T...mentioning
confidence: 99%
“…Likewise, it is necessary to create an accurate and up-to-date database of the role the major consuming countries take in terms of numbers of wild caught/farmed animals, supplying countries, harvest locations, farms involved (cf. with data records of the Law Enforcement Management Information System, LEMIS), mortality figures, etc., with a focus on the European Union (EU) (Veith et al 2000;Potočnik 2012;Çiçek et al 2021) and Switzerland (see Dubey et al 2014;Dufresnes et al 2018). For example, TRACES is an online platform of the EU established to certify imports of animals and their products according to sanitary standards (https://ec.europa.eu/food/animals/traces_en, see Suppl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation